APPLICATION OF TALKING CHIPS LEARNING MODEL TO IMPROVE ACTIVITIES AND RESULTS OF CHEMICAL LEARNING IN MAN 13 JAKARTA - Diyah Fitri Rhochani; Kurroti Ayun (Universitas Negeri Surabaya, 2018)
This study aims to determine the increase in activity and learning outcomes of Chemistry in the material of chemical bonds by applying the Talking Chips learning model. The subject of this study were students of 10th grade in MIA-2 class of MAN 13 Jakarta with a total of 31 students in the odd semester of 2017/2018 school year. This study uses classroom action research (CAR) method which consists of two cycles, each cycle consists of four stages. Data collection techniques used are tests of student learning outcomes in each cycle as well as observation sheets of student and teacher activities. The results showed that the completeness of learning criteria had been achieved by increasing the average student learning outcomes from cycle I by 68% to 97% and in cycle II it had increased by 29%. Increases also occur in student learning activities with an increase in value of each from cycle I by 61% to 85% in cycle II. Based on the results of these studies, it can be said that by using the Talking Chips learning model, student activities and learning outcomes can be improved.